The Relationship Between Self-Esteem and Assertive Behavior Among Members of Student Organizations at Muhammadiyah University of Gorontalo - Lenny Syamsuddin; Rahmawaty Parman; Shulistia Syah Buna (PSPP JOURNALS, 2026)
This study aims to determine the relationship between self-esteem and assertive behavior among members of student organizations at the University of Muhammadiyah Gorontalo. Self-esteem is an individual's subjective assessment of themselves, while assertive behavior is an individual's ability to express feelings, opinions, and personal rights honestly and openly without harming others. This study used a quantitative correlational method with a sample of 195 students who are members of campus organizations, selected using a simple random sampling technique. The instruments used were a self-esteem scale and an assertive behavior scale compiled based on the theories of Coopersmith and Alberti & Emmons. Data analysis was conducted using normality, linearity, and Pearson Product Moment correlation tests. The results of the analysis showed a positive and significant relationship between self-esteem and assertive behavior, with a correlation value (r) of 0.325 and a significance value (p) = 0.000 (p < 0.05). This means that the higher a person's self-esteem, the higher their assertive behavior. This study concludes that self-esteem plays a role in shaping assertive behavior, although it is not the only factor influencing it.